Anisotropy of the surface of carbon materials - Yurov, V.M.; Goncharenko, V.I.; Oleshko, V.S.; Sha Minggong (Eurasian Physical Technical Journal, 2021)
In this work, a model of the surface layer of perfect single crystals is used and the role of surface energy in physical processes occurring in the region of nanosized carbon materials is clarified. Of these, diamond, graphite, carbyne and fullerenes have been investigated. The thickness of the surface layer of diamond with cubic symmetry is 8.2 nm and is a nanostructure. The average size of the synthesized nanodiamond is of the order of ~ 8 nm. The value of the surface energy σhkl calculated by us along the diamond planes (100), (110), and (111) is in good agreement with experiment and other calculations. The thickness of the surface layer of graphite along the a axis is equal to R(I)a = 8.0 nm and also represents a nanostructure. But along the c axis we have a layer thickness of about 1.5 nm and the number of monolayers is only 2. On this c axis, graphite can be created a monolayer by turning it into graphene. The σhkl value calculated by us along the a and c planes of graphite is 25957 and 5515 mJ/m2, respectively. Carbines represent a polymeric polyyne or cumulene chain composed of sp-hybridized carbon atoms. If we imagine that the thickness of the surface layer of carbyne is stretched into a one-dimensional chain along the c axis, then the length of this chain is up to 200 nm for α-carbyne. The thickness of the surface layer of fullerenes significantly exceeds the thickness of the surface layer of pure metals. The surface energy of fullerenes σhkl increases with an increase in the number of carbon atoms С36 → С96. It also changes in the series (111) → (100) → (110).
Keywords: diamond; graphite; carbyne; fullerenes; nanostructures; surface layer thickness; surface energy; anisotropy